Refleksi Konsep Proto Logos Lukas dalam Membangun dan Meningkatkan Kegiatan Publikasi Ilmiah di Lingkungan Sekolah Tinggi Teologi - Siahaan, Harls Evan R. (Sekolah Tinggi Agama Kristen Negeri Toraja, 2018)
The activity of scientific publication is an academic reflection in the field of higher education. This activity has been increasing significantly in the last two years, especially with the regulations of the ministry of research and higher education which regulated publishing research issues in the online journals. Theological College as a higher education under the Ministry of Religion is not immune to the effects of regulations concerning scientific journals. This article aimed to show a biblical reflection on building and improving scientific publications. By using a descriptive analysis method on the text of Luke 1:1-4, the conclusion obtained is that the writing process of the Gospel of Luke reflected the phases of scientific publication, so that it could become a theological reflection for theological colleges to carry out academic activities in building and improving publication activities through online journals.Abstrak: Kegiatan publikasi ilmiah merupakan sebuah refleksi aktivitas akademis di lingkungan sekolah-sekolah pendidikan tinggi. Kegiatan ini telah mengalami eskalasi yang siginifikan dalam dua tahun belakangan, terlebih lagi dengan munculnya peraturan kementrian riset dan pendidikan tinggi yang mengatur publikasi penelitian dalam bentuk jurnal online. Sekolah Tinggi Teologi sebagai pendidikan tinggi yang berada di bawah Kementrian Agama tidak luput dari imbas peraturan yang menyangkut jurnal ilmiah. Artikel ini bertujuan untuk menunjukkan sebuah refleksi biblikal untuk membangun serta meningkatkan publikasi ilmiah. Dengan menggunakan metode analisis deskriptif pada teks Lukas 1:1-4, maka diperoleh kesimpulan bahwa proses penulisan Injil Lukas merefleksikan fase-fase publikasi ilmiah, sehingga hal ini menjadi sebuah refleksi teologis bagi Sekolah-sekolah Teologi untuk melakukan kegiatan akademis membangun dan meningkatkan kegiatan publikasi ilmiah melalui jurnal online.